Non-Voting Party and Wage Inequalities: Long-Term Evidence from Italy - Armanda Cetrulo; Margherita Lanini; Angelica Sbardella; Maria Enrica Virgillito (Intereconomics, 2023)
By means of a long-run analysis on electoral and inequality data, this article shows that there exists a temporal correlation between inequalities and non-voting behaviour. Non-voting is progressively becoming a widespread phenomenon, beyond specific national contexts, and challenges the functioning of democracies in advanced capitalist countries. Notably, data on electoral results in Italy do not show a clear leading group of non-voters. Although historically concentrated in southern Italy and predominantly female, non-voters are proportionally increasing in the centre and in the north of the country, independently of the gender dimension. The root causes of the phenomenon should be traced back not only to the political and institutional dimension, but also to a widespread socio-economic determinant, namely labour market inequality, the driver addressed in this article.
Keywords: D33; D72; P1; 330